Endowed or Owned? Theorising Ownership Status as a Governance Antecedent in the Management of Indonesian Pesantren - Ali Muhlisin; Zulkiple Abd Ghani; Muhamad Towil Akhirudin (Educazione: Journal of Education and Learning, 2025)
Ownership of the institutional asset base is among the most consequential yet least theorized features of Indonesian pesantren. This article asks how ownership status conditions governance arrangements and core management practices. It applies a structured conceptual review with thematic synthesis, informed by PRISMA 2020 reporting logic, to 62 scholarly and documentary sources published between 2010 and 2025 and retrieved from Scopus, Web of Science, Google Scholar, Indonesian indexing portals, and institutional grey literature. Coding proceeded through inductive theme identification, analytic clustering, and framework construction across two iterative passes. The synthesis produced six themes and four mechanism families that position ownership status as a foundational governance condition rather than a legal formality. The resulting framework links three ownership configurations, waqf khayri, waqf ahli or family-stewardship arrangements, and non-waqf control, to authority structure, accountability direction, stakeholder oversight, and rule formalization, and through these to decision-making, asset and financial management, leadership succession, and strategic planning. Five contextual moderators are specified, among which digital capability sharply lowers the transaction cost of formal accountability. Seven testable propositions and an operationalization agenda are advanced for comparative and multiple-case research. The framework offers pesantren leaders, nazhir bodies, and policy stakeholders a differentiated basis for governance reform.